2015
DOI: 10.1021/acs.iecr.5b03425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcination Temperature on the Structure and Catalytic Performance of the Ni/Al2O3 and Ni–Ce/Al2O3 Catalysts in Oxidative Dehydrogenation of Ethane

Abstract: We studied the effect of calcination temperature of Ni/Al 2 O 3 and Ni−Ce/Al 2 O 3 catalysts on the specific surface area, acidity, ratio of pore volume and specific surface area, reducibility reflecting the changing population of Ni(T d ) and Ni(O h ) species, and activity/selectivity in oxidative dehydrogenation of ethane. It should be stressed that the role of Ce as a promoter on the catalytic activity of Ni−Ce/Al 2 O 3 catalysts decreased with an increasing value of the calcination temperature. At a reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 55 publications
4
16
0
Order By: Relevance
“…% Ni 0.5 -Ce 0.5 /γ-Al 2 O 3 catalysts. It shows that a peak at about 535˝C is observed and it has been reported that the presence of Ce improves Ni dispersion, thus promoting the reduction of nickel species [48][49][50]. Incidentally, the reduction peak could be assigned to the strong interaction between NiO and CeO 2 .…”
Section: Temperature Program Reduction (Tpr)mentioning
confidence: 81%
“…% Ni 0.5 -Ce 0.5 /γ-Al 2 O 3 catalysts. It shows that a peak at about 535˝C is observed and it has been reported that the presence of Ce improves Ni dispersion, thus promoting the reduction of nickel species [48][49][50]. Incidentally, the reduction peak could be assigned to the strong interaction between NiO and CeO 2 .…”
Section: Temperature Program Reduction (Tpr)mentioning
confidence: 81%
“…As the calcination temperature may play an essential role for the kinetics of the reaction, the obtained catalysts were evaluated for the oxidation of benzyl alcohol. The catalyst calcined at 300 °C [ ZrO x (1 %)–MnCO 3 ] yielded a 100 % conversion of benzaldehyde with 13.33 mmolg −1 h −1 specific activity and 164.27 h −1 turnover frequency ( TOF ), within 30 min of the reaction, whereas the catalyst calcined at 500 °C [ ZrO x (1 %)–Mn 2 O 3 ] yielded a 21.53 % conversion within the first 30 min (Figure ) with 2.87 mmolg −1 h −1 specific activity and 35.37 h −1 TOF (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…As the calcination temperature may play an essential role for the kinetics of the reaction, [24] the obtained catalysts were evaluated for the oxidation of benzyla lcohol. To investigate the optimum amount of ZrO x presenti nM nCO 3 to effect the kineticso ft he reaction, catalystsp repared by varying the amount of ZrO x precursor from 1t o7 %w ere tested for the oxidation of benzyla lcohol to benzaldehyde.…”
Section: Effect Of Calcination Temperaturementioning
confidence: 99%
“…This trend was explained by the fact that the solid–solid interaction between γ−Al 2 O 3 and the transition metal oxide affects the state of the transition metal, thus affecting the catalytic activity in CO oxidation. One of the currently used solutions to improve the catalytic performance of the Ni–, Cu– or Co−γ−Al 2 O 3 catalyst systems is the addition of rare-earth metal oxides (CeO 2 , La 2 O 3 ) or alkaline earth metal oxide (MgO, CaO) as promoters [ 9 , 10 , 11 , 14 , 15 ]. Another method has been proposed is the addition of a second active metal/metal oxide phase into the catalyst.…”
Section: Introductionmentioning
confidence: 99%